2020
DOI: 10.1186/s12879-020-4794-5
|View full text |Cite
|
Sign up to set email alerts
|

Impaired consciousness and decreased glucose concentration of CSF as prognostic factors in immunocompetent patients with cryptococcal meningitis

Abstract: Background: Cryptococcal meningitis (CM) is the most common fungal infection of the central nervous system and has high morbidity and mortality. Almost studies about prognostic factors have largely focused on the immunocompromised population rather than immunocompetent patients. So that we sought to conduct a retrospective study to determine prognostic factors which predict the outcomes in immunocompetent patients with CM. Methods: We retrospectively collected and analyzed the demographic and clinical data of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 34 publications
4
15
0
1
Order By: Relevance
“…Moreover, in the present study, the most common symptoms included headache, fever, weakness, lethargy, cough, and sputum. This was partially in line with the results of a research conducted by Zhang et al [ 15 ] who reported headache, fever, and emesis as the most common symptoms. Besides, this is consistent with the findings of the study carried out by Lee et al who mentioned headache, fever, and altered state of consciousness as the most common symptoms [ 12 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, in the present study, the most common symptoms included headache, fever, weakness, lethargy, cough, and sputum. This was partially in line with the results of a research conducted by Zhang et al [ 15 ] who reported headache, fever, and emesis as the most common symptoms. Besides, this is consistent with the findings of the study carried out by Lee et al who mentioned headache, fever, and altered state of consciousness as the most common symptoms [ 12 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, the glucose level of CFS was not associated with the increase in the mortality rate. On the other hand, Zhang et al reported decreased glucose concentration of CSF as an effective factor on the increase of mortality [ 15 ]. Generally, it was not possible to compare the findings of this research with those of other studies due to the small population of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our data indicated that altered consciousness was strongly associated with cryptococcemia outcome in patients with and without HIV infection. It was previously noted that severe fungemia and cryptococcal meningitis both resulted in altered consciousness, 39,40 and altered consciousness is recognised as a predictor associated with unfavourable outcomes in patients with cryptococcosis 41,42 . In our study, all patients exhibited fungemia, and 71.5% patients exhibited cryptococcal meningitis.…”
Section: Discussionsupporting
confidence: 49%
“…It was previously noted that severe fungemia and cryptococcal meningitis both resulted in altered consciousness, 39,40 and altered consciousness is recognised as a predictor associated with unfavourable outcomes in patients with cryptococcosis. 41,42 In our study, all patients exhibited fungemia, and 71.5% patients exhibited cryptococcal meningitis. Therefore, it is conceivable that altered consciousness could serve as an indicator of cryptococcemia prognosis.…”
Section: It Has Long Been Noted That Hiv Infection Is Associated Withsupporting
confidence: 50%
“…Son levaduras encapsuladas que se reproducen por gemación y que pueden ocasionar enfermedad tanto en personas inmunocompetentes como inmunocomprometidas. Frecuentemente estas levaduras afectan al Sistema Nervioso Central (13,14).…”
Section: Introductionunclassified